Traffic-related-air-pollutant PM2.5 Caused Toxicity on Caenorhabditis elegans with Cotreatment of High-dose Glucose and Tempeh - Jian-He Lu; Ming-Hsien Tsai; Sen-Ting Huang; Jia-De Lee; Ta-Chih Hsiao; Wan Nurdiyana Wan Mansor; How-Ran Chao (Aerosol and Air Quality Research)
Abstract Rapid economic development and urbanization have significantly increased PM2.5-induced and hyperglycemia-induced toxicological effects. Tempeh is a traditional Indonesian food and may be beneficial for patients with type II diabetes. However, the toxicological effects of co-exposure to traffic-related-air-pollutant (TRAP) PM2.5 with high glucose and the potential therapeutic effect of tempeh remain unclear. Using Caenorhabditis elegans (C. elegans) as an in vivo animal model, we found that exposure to 12.74 mg L−1 TRAP PM2.5 and 80 mM D-glucose could induce toxicity in nematodes that affects growth, reproduction, locomotion behavior, and lifespan. Moreover, TRAP PM2.5 and high glucose diet co-treatment reinforced these adverse effects on C. elegans. However, pretreatment with 200 µg of tempeh extract had the greatest improvement in the adverse effects of treatment with or without 12.74 mg L−1 TRAP PM2.5 and with or without 80 mM D-glucose on C. elegans. In addition, tempeh treatment also ameliorated the altered mRNA expression of the antioxidant gene in C. elegans treated with or without TRAP PM2.5 and with or without high-dose glucose diets. These findings reveal that co-exposure to TRAP PM2.5 and high-dose glucose causes more serious health effects, while tempeh could modulate oxidative stress which ameliorated TRAP PM2.5-induced and hyperglycemia-induced toxicological effects.